Developing a web-based system for coordinating school-based care for students with social, emotional, and behavioral problems - Evans, Steven W.; Brockstein, Hannah; Allan, Darcey M.; Girton, Sam L.; Owens, Julie Sarno; Everly, Elise L. (Frontiers in Education, 2022)
Many students with social, emotional and behavioral problems receive school-based services. Multi-Tiered System of Support (MTSS) is the one most frequently referenced systems for coordinating services. The goal of this framework is to effectively match assessment and services to the needs of individual students. In many schools this process is limited by a lack of an overall coordinating system. As a result, many students receive services for social, emotional and behavioral problems that are unlikely to be effective, are not guided by progress monitoring, and not adequately informed by current and historical data. The Beacon System is a web-based tool created to enhance the quality of service provision for students with social, emotional, and behavioral problems by supporting continuous progress monitoring, helping educators know what services are likely to be helpful for a particular student according to their age and presenting problems, and providing educators and school mental health professionals with information to help them implement both familiar and unfamiliar interventions. Additionally, the Beacon system will enhance educators’ abilities to coordinate with a student’s entire intervention team and allow for continuity as a child changes grades, teachers, or schools. Enhancing these parts of the overall process can improve educators’ efforts to achieve the goals of MTSS to provide effective interventions matched to the students’ needs. The purpose of this manuscript is to describe the iterative development process used to create Beacon and highlight specific examples of some of the methods. In addition, we will describe how feedback from stakeholders (e.g., teachers, school mental health professionals) was used to inform decisions about design. Finally, we will describe the final development steps taken prior to pilot implementation studies and our plans for additional data collection to inform continued development of Beacon. This includes the strategies being used to measure outcomes at multiple levels including assessing a variety of behaviors of the professionals in the schools as well as student outcomes. These data will inform continuous development work that will keep us moving towards our goal of enhancing the outcomes of students with social, emotional and behavioral problems.